Enhancement of temperature diagnostics with application to dynamically compressed materials - Ota, T (2019)
The behaviour of materials at high pressure is relevant for a number of fields, including defence, aerospace and Earth and planetary science where understanding of material behaviour under high strain-rate conditions such as impacts is required. State variables such as pressure and density are readily accessible in shock experiments but determination of temperature remains challenging.